Effect of previous utilization and out-of-pocket expenditure on subsequent utilization of a state led public-private partnership scheme "Chiranjeevi Yojana" to promote facility births in Gujarat, India - Sandul Yasobant; Hemant Deepak Shewade; Kranti Suresh Vora; Kristi Sidney Annerstedt; Petros Isaakidis; Nishith B. Dholakia; Dileep V. Mavalankar (BMC, 2017)
Abstract Background In Gujarat, India, a state led public private partnership scheme to promote facility birth named Chiranjeevi Yojana (CY) was implemented in 2005. Institutional birth is provided free of cost at accredited private health facilities to women from socially disadvantaged groups (eligible women). CY has contributed in increasing facility birth and providing substantially subsidized (but not totally free) birth care; however, the retention of mothers in this scheme in subsequent child birth is unknown. Therefore, we conducted a study aimed to determine the effect of previous utilization of the scheme and previous out of pocket expenditure on subsequent child birth among multiparous eligible women in Gujarat. Methods This was a retrospective cohort study of multiparous eligible women (after excluding abortions and births at public facility). A structured questionnaire was administered by trained research assistant to those with recent delivery between Jan and Jul 2013. Outcome of interest was CY utilization in subsequent child birth (Jan-Jul 2013). Explanatory variables included socio-demographic characteristics (including category of eligibility), pregnancy related characteristics in previous child birth, before Jan 2013, (including CY utilization, out of pocket expenditure) and type of child birth in subsequent birth. A poisson regression model was used to assess the association of factors with CY utilization in subsequent child birth. Results Of 997 multiparous eligible women, 289 (29%) utilized and 708 (71%) did not utilize CY in their previous child birth. Of those who utilized CY (n = 289), 182 (63%) subsequently utilized CY and 33 (11%) gave birth at home; whereas those who did not utilize CY (n = 708) had four times higher risk (40% vs. 11%) of subsequent child birth at home. In multivariable models, previous utilization of the scheme was significantly associated with subsequent utilization (adjusted Relative Risk (aRR): 2.7; 95% CI: 2.2-3.3), however previous out of pocket expenditure was not found to be associated with retention in the CY scheme. Conclusion Women with previous CY utilization were largely retained; therefore, steps to increase uptake of CY are expected to increase retention of mothers within CY in their subsequent child birth. To understand the reasons for subsequent child birth at home despite previous CY utilization and previous zero/minimal out of pocket expenditure, future research in the form of systematic qualitative enquiry is recommended.